The Effect of Work Supervision, Competence and Work Motivation On Work Discipline of Rattan Industry Employees PT. Totum Diba Cirebon Regency - Fahri Muhamad Riyandi; Ryalnaldi Putra Permana; Alfanda Pratama; Noveria Susijawati (Journal Research of Social Science, Economics, and Management, 2024)
In company, nothing succeeds if it does not have disciplined employees. Work Discipline guarantees the implementation of tasks in orderly and smooth manner so as achieve optimal results. The purpose of this study is to determine the significant relationship between the influence of work supervision, competence and motivation on the work discipline of rattan industry employees of PT. Totum Diba, Cirebon Regency. In this study the research approach used was quantitative approach with survey / questionnaire method, and the data was tested using multiple linear regression test. The sample in this study is employees of PT. Totum Diba, Cirebon Regency totaled 160 respondents. The findings show that the sig value for the effect of Work Supervision (X1) Work Discipline has a positive influence of Work Supervision (X1) Work Discipline (Y), then it is known that the sig value for the influence Competence (X2) on work discipline (Y) that there is no influence for Competence (X2) work discipline (Y), and it is known that the sig value for the influence Motivation (X3) on Work Discipline (Y) there is a positive influence for Motivation (X3) on work discipline (Y). Based on the data, Work Supervision, Competence, and Work Motivation The results of multiple linear regression analysis show significance, This means that there is a simultaneous and significant influence on Work Discipline. Therefore, the level of work discipline is positively influenced by effective work supervision, high level of competence, and strong work motivation towards the Work Discipline of PT. Totum Diba, Cirebon Regency.